2020
DOI: 10.1001/jamadermatol.2019.3839
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Safety of Oral Propranolol Therapy in Patients With PHACE Syndrome

Abstract: IMPORTANCEOral propranolol is widely considered to be first-line therapy for complicated infantile hemangioma, but its use in patients with PHACE (posterior fossa malformations, hemangioma, arterial anomalies, cardiac defects, eye anomalies) syndrome has been debated owing to concerns that the cardiovascular effects of the drug may increase the risk for arterial ischemic stroke.OBJECTIVE To assess the incidence of adverse events among patients with PHACE syndrome receiving oral propranolol for infantile hemang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 16 publications
1
30
0
1
Order By: Relevance
“…Numerous studies have shown that large, thick hemangiomas, such as those seen in PHACE, are at overall higher risk for ulceration. 12 Propranolol is known to inhibit vasculogenesis, and ulceration occurs when the blood supply to the epidermal surface of the hemangioma is compromised. Preliminary data from the May 2020 international meeting of the Internal Society for the Study of Vascular Anomalies presented by Faith and colleagues 13 suggests that a lower dose propranolol and a slower up-titration reduce the risk of ulceration.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that large, thick hemangiomas, such as those seen in PHACE, are at overall higher risk for ulceration. 12 Propranolol is known to inhibit vasculogenesis, and ulceration occurs when the blood supply to the epidermal surface of the hemangioma is compromised. Preliminary data from the May 2020 international meeting of the Internal Society for the Study of Vascular Anomalies presented by Faith and colleagues 13 suggests that a lower dose propranolol and a slower up-titration reduce the risk of ulceration.…”
Section: Discussionmentioning
confidence: 99%
“…BAR antagonists (beta blockers) are increasingly used topically to treat skin diseases. The non-specific antagonists for beta AR such as propranolol and timolol, are widely used for treating infantile hemangiomas [36][37][38][39]. Topical application of timolol is used to treat a host of dermatologic diseases [40,41], including epidermolysis bullosa [42], Kaposi sarcoma [43,44], acne and acne rosacea [45], and improving scar outcomes [46].…”
Section: Discussionmentioning
confidence: 99%
“…Clásicamente se ha cuestionado la seguridad del propranolol en estos pacientes ya que el uso de β-bloqueantes en el contexto de la vasculopatía cerebral podría, teóricamente, aumentar el riesgo de un episodio isquémico cerebral. Sin embargo, recientemente Olsen y col publicaron un estudio multicéntrico retrospectivo con 76 pacientes con síndrome de PHACE tratados con propranolol vía oral sin encontrar diferencias significativas en la tasa de eventos adversos severos (ictus, accidentes cardiovasculares e isquémicos transitorios) respecto a aquellos que solo tenían la lesión vascular cutánea (0% vs 0,4%, respectivamente) 16 .…”
Section: Discussionunclassified